Distribution of pathological types and epidemiological characteristics based on kidney biopsy in Northwest China - Yunlong Qin; Jin Zhao; Xiao Wei; Yuwei Wang; Zixian Yu; Yumeng Zhang; Shiren Sun (The Korean Society of Nephrology, 2023)
Background The spectrum of biopsy-confirmed kidney disease varies with regions and periods. We describe the distribution of pathological types and epidemiological characteristics of kidney diseases in Northwest China due to regional differences in geographical environment, social economy, and dietary habits. Methods Kidney biopsy cases from 2005 to 2020 in Xijing Hospital were retrospectively analyzed. Pathological characteristics of patients in different periods were analyzed using the t test or chi-square test. Joinpoint regression was used to analyze trends in pathological types and disease spectrum. Results A total of 10,528 eligible patients were included. Primary glomerular disease (PGD) accounted for the majority of the cases and exhibited an obvious downward trend, whereas secondary glomerular disease (SGD) showed an obvious upward trend. Among PGD, immunoglobulin A nephropathy (IgAN) remained the most common pathological type, and the detection rate of membranous nephropathy (MN) was significantly increased. Among SGD, Henoch-Schönlein purpura nephritis (HSPN) was the most common pathological type and may present a significant characteristic of Northwest China. Diabetic nephropathy (DN) exhibited the most obvious upward trend in the whole process, whereas the fastest growth since 2012 was in hypertensive nephropathy. Conclusion The proportion of SGD increased whereas PGD declined. IgAN remained the most common PGD, and HSPN was the most common SGD. MN and DN showed the most obvious upward trend among PGD and SGD, respectively. Changes in the spectrum of kidney disease, especially the constituent ratio of SGD, pose a great challenge to public health.